Determinan Kinerja Perusahaan Perbankan di BEI Tahun 2019-2023 - Qhotimah, Qhusnul; Kartika Hendra Titisari; Sari Kurniati (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This research was conducted to test and analyze the quality of external audits, audit committee characteristics, the role of female commissioners, management control systems, and real profit management on company performance. The data source used is secondary data obtained from the financial reports of banking companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. The population of this research is banking companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. Sampling used a purposive sampling method and the sample used in this research was 26 companies. The data analysis technique uses multiple linear regression analysis processed with SPSS version 21. The research results show that the quality of the external audit, the role of the female board of commissioners, and real earnings management have an influence on company performance, while the characteristics of the audit committee and the management control system have no effect on company performance.